EVALUASI KONDISI ANGKUTAN MASAL DI JABODETABEK AKIBAT PSBB - Lensi Oktavia Stini (Journal of Civil Engineering and Planning (JCEP), 2020)
Jabodetabek development has had an impact on the supporting transportation system, the more developed Jabodetabek, the more developed the existing transportation system. But at this time in various countries in the world there is an outbreak of Covid-19 which has a major impact on all aspects. In Indonesia a system has been set up aimed at suppressing the expansion of the Covid-19 outbreak by implementing a Large-Scale Social Restrictions (PSBB) system. Large-scale social restrictions are restrictions on certain activities of residents in an area suspected of being infected with Corona Virus Disease 2019 (COVID-191 in such a way as to prevent the possibility of spreading Corona Virus Disease 2019 (COVID-I9). Large-scale Social Restrictions must be based on epidemiological considerations, the magnitude threats, effectiveness, support of resources, operational technical, political, economic, social, cultural, defense and security considerations.The impact of the PSBB is strongly felt in aspects of the existing transportation system, therefore there is a need to study "Jabodetabek Transportation System in the Cons PSBB ". This research uses descriptive analysis. This method is used to identify the impacts that are influenced by factors that are happening. Based on the analysis that has been done, it is known that the Jabodetabek transportation system service during the PSBB implementation based on the existing influence factor is the public transportation system in Jabodetabek felt the overall impact such as railroad tracks, public buses, conventional taxis and online taxis and motorcycle taxis. This public transportation service system is limited in terms of operating time and passenger restrictions, so this condition is not good for many people because it also impacts on the weakening of the economy, reduction in transportation modes and passenger congestion. So that this condition is not good in various aspects, but the influence factor is aimed at suppressing the spread of Covid-19 which is still endemic in Indonesia, especially in the Jabodetabek area which has become a red zone. The decrease in the number of passengers occurred since January 2020, starting on April 15, 2020 the number of passengers decreased significantly, namely 78.70% in KRL, 90.12% in TransJakarta, 94.12% in MRT, 93.05% in LRT, 64.71% in Taxi and 58.33% in taxibike. Keywords: Transportation System, Covid-19 Impact, Large-Scale Social Limitation.